Rational Pharmacotherapy Management Process in Dentistry - AKICI, AHMET; GÖÇMEN, GÖKHAN (MARMARA UNIV, FAC PHARMACY, 2017)
Unnecessary or improper use of medications is a common worldwide problem. Inadequate approach of doctors to the rational use of medicine (RUM) principles and lack of its educational process are main reasons of this problem. RUM defined as patients receive medications appropriate to their clinical needs, in doses that meet their own individual requirements, for an adequate period of time, and at the lowest cost to them and their community. Dentists prescribe serious amount of medication, which is mostly analgesics and antibiotics. Therefore, informing dentists and dissemination of RUM among them is an urgent issue. This article points out, how to manage overall treatment process based on RUM principles next by a patient on the dental practice. In additionally, that is carried out by a simulation case requiring an analgesic drug treatment. Therefore, suitability of the drug with the patient, which is going to be prescribed after dental procedure with the correct diagnosis, will be assessed. Illness, treatment aim, participants and adaptation with the life style are explained to the patients. Dentist makes instructions and recommendations clearly about the pharmacotherapy process and informs the patient. Therefore, they integrate the patient to the overall treatment process and manage it.
Keywords: Rational use of medicine; Dentist; Graduation; Rational pharmacotherapy; Education; DRUGS NSAIDS; ANTIBIOTICS; ATTITUDES; PATTERN